Recommendations for management of Diabetes and its complications during Holy Hajj - Fariduddin, Md; Gaffar, Md Abu Jar (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Abstract not available J Assoc Clin Endocrinol Diabetol Bangladesh, January 2022; 1 (1): 22-23